A NEW SPECIES OF PARABOEA (GESNERIACEAE) FROM THAILAND - Puglisi, C.; Phutthai, T. (Edinburgh Journal of Botany, 2017)
A new species of Paraboea, P. fimbriata C.Puglisi & Phutthai, from Sai Yok District, Kanchanaburi Province, Thailand, is described.
Keywords: Kanchanaburi; limestone; taxonomy